Enhancement of the Yersinia pestis EV NIIEG Vaccine Srain Immunogenic and Protective Activity under Cultivation with Azoxymer Bromide (Polyoxidonium) - T. N. Shchukovskaya; A. Y. Goncharova; S. A. Bugorkova; O. M. Kudryavtseva; N. E. Shcherbakova; A. S. Abdrashitova (Эпидемиология и вакцинопрофилактика, 2022)
Background. The live-attenuated vaccine based on the Yersinia pestis strain EV line NIIEG is still used in Russia, providing protective efficacy against plague. Nevertheless, there is an urgent need for developing new ways to increase the immunogenicity of the Y. pestis EV NIIEG vaccine strain. In this study, the ability of direct action of immunoadjuvant azoximer bromide (polyoxidonium, PO) on the immunobiological properties of vaccine strain Y. pestis EV NIIEG during cultivation on a dense nutrient medium was evaluated. Materials & Methods. Y.pestis EV NIIEG, cultivated at 28 °С for 48 h on LB agar, Miller pH 7.2 ± 0.1 (Sigma-Aldrich, USA) with the addition of PO and without. MALDI-TOF mass-spectrometry was deployed for the obtainment of mass-spectra of ribosomal proteins from Y. pestis EV NIIEG cells on the MicroflexTM LT mass spectrometer (Bruker Daltonics, Germany). Protective efficacy was evaluated under subcutaneously challenge guinea pigs and mice BALB's with 400 LD50 doses of the Y. pestis 231, Y. pestis P-13268 Vietnam (MLD=5 CFU). Antibody titers to F1 in serum were determined using an ELISA. Results. The addition of the therapeutic concentration of PO in the cultivation medium induced a significant increase in the immunogenicity of Y. pestis EV NIIEG that resulted in enhancement of serum antibody levels against Y. pestis F1 antigen and several times the growth of protective efficacy in the bubonic plague model on two types of experimental animals. ImD50 of the vaccine strain Y. pestis EV NIIEG, cultivated with PO, was significantly (p < 0,05) lower in comparison to ImD50 for Y. pestis EV NIIEG in standard cultivation conditions. One year of storage at a temperature of 4 °С did not alter the protective properties of the vaccine strain Y. pestis EV NIIEG, cultivated with PO. Conclusions. Morphological studies confirmed the absence of influence PO introduction into the cultivation environment on the safety of the vaccine strain. MALDI-TOF MS profile of the Y. pestis EV NIIEG, cultivated with PO, had peaks characteristic features. The mass peak at m/z 3,061 was significantly down-regulated and new mass peaks at m/z 2,759, m/z 3,533 were determined. These changes are accompanied by the increase of Y. pestis EV NIIEG immunogenicity.